Legal responsibility in the structure of the legal status of foreigners and stateless persons (Bulletin of Kharkiv National University of Internal Affairs, 2022)
The article is devoted to an important and topical issue, that is the essence of legal responsibility as a structural element of the legal status of foreigners and stateless persons. It is noted that the concept of “responsibility” is used by many branches of scientific knowledge, which imbue it with a peculiar meaning determined by their subject. In a broad sense, responsibility is a special relationship between human actions (people, institutions), intentions, as well as evaluations of these actions by other people or society.It has been proven that social responsibility depends on the sphere of social activity, in connection with which political, moral, social, legal and other types of responsibility are distinguished. Social and legal responsibility are related as a genus and species. The issue of responsibility is relevant not only for the theory of law, but also for all branches of science, as it is essential for understanding the essence and role of the legal status of a person in general and of a foreigner and stateless person in particular.Three key approaches to the interpretation of the concept of “legal responsibility” are analyzed, namely: retrospective, positive and two-aspect. According to the first, legal responsibility is the legal obligation of the offender to suffer adverse consequences determined by the state for the illegal act committed by him or her. According to the second, legal responsibility is lawful behavior, the obligation to comply with prohibitions, the fulfillment of positive duties, as well as the permissions granted and guaranteed by the state for the exercise of subjective rights, the use of state incentives, recognition. The third approach assumes that retrospective legal responsibility results from a breach of positive legal responsibility.
Keywords: legal status; foreigners; stateless persons; legal responsibility; element of legal status.